The Preventive Oral Supplementation of a Selenium Nanoparticle-enriched Probiotic Increases the Immune Response and Lifespan of 4T1 Breast Cancer Bearing Mice - Yazdi, M. H.; Mahdavi, M.; Kheradmand, E.; Shahverdi, A. R. (Arzneimittelforschung, 2012)
The immunomodulatory effects of lactic acid bacteria have been demonstrated previously. In this study, a Lactobacillus plantarum strain was selected and enriched with selenium nanoparticles for use as a new immunomodulating agent in a breast cancer murine model. 30 female inbred BALB/c mice were equally divided into a test group and a control group. For 2 weeks prior to tumor induction, each mouse received a daily oral administration of 2.5×108 CFU/ml of L. plantarum enriched with selenium nanoparticles (SeNPs), and then 1×106 4T1 cells were injected subcutaneously. After tumor induction, daily SeNP administration was repeated for 3 cycles of 7 days on/3 days off. Immunological parameters such as levels of cytokines, NK cell activity, tumor growth, and mouse survival were evaluated. The production of the pro-inflammatory cytokines IFN-γ, TNF-α, and IL-2 in spleen cell cultures was increased in test mice administered SeNP-enriched L. plantarum. The test mice also showed significant increases in NK cell activity. The tumor volumes of treated mice were decreased and their survival rate notably increased when compared to mice that received L. plantarum alone or control mice. Administration of SeNP-enriched L. plantarum can induce an efficient immune response through the elevation of the pro-inflammatory cytokines IFN-γ, TNF-α and IL-2 levels and increased NK cell activity. Therefore, this treatment may result in better cancer prognosis.
Keywords: 4T1 breast cancer cell; selenium nanoparticle; Lactobacillus plantarum; NK cell activity; pro-inflammatory cytokine